التسير التنبئي للمنصب والكفاءات في المؤسسة GPECدور - لكحل, أمينة (My University, 2022)
As a result of the transformations and challenges that economic institutions are witnessing from the intensification of competition and the acceleration of technology, human resource management is emerging as a main tributary and an effective pillar for achieving integration in the current environment based on quality, knowledge and intense reliance on human competencies, those competencies that play a key role in various activities and jobs within the organization. Accordingly, the predictive management of positions and competencies is considered a vital tool that enables the organization to control to some extent the future and face the changes of the environment in its quest to achieve consistency between its future needs for positions as well as competencies in quantity, quality and time. From this point of view, human resources were interested in the predictive management of positions and competencies, believing in their role in activating their various activities and improving their performance. In this study, we will touch the most important points related to human competencies as well as the predictive management of positions and competencies, and then we will address also a field study at the level of the institution for the management of fishing ports and shelters.
مستغانم EGPPدراسة ميدانية لمؤسسة تسير موانئ وملاجئ الصيد البحري
Keywords: Human resources, human competencies, performance, predictive management of positions and competencies, typical job.